Flame-made Nb-doped zinc oxide nanoparticles for application in polymer solar cells - Viruntachar Kruefu (2018)
Flame spray pyrolysis (FSP) is a very promising technique for synthesis of high purity nano-sized materials with controlled size and crystallinity in one step. FSP was employed to synthesize pure ZnO and niobium-doped ZnO (Nb/ZnO) nanoparticles containing 0.1-4 mol% Nb. ZnO is one of the most versatile and most widely applied as catalytic metal oxide. Precursor solutions of zinc naphthenate and niobium (V) ethoxide in toluene/methanol (70/30 vol%) were sprayed and combusted, resulting in crystalline and nanostructured particles. The crystalline phase, morphology and size of the nanoparticles were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The specific surface area of the nanoparticles was measured by nitrogen adsorption (BET analysis). The ZnO nanoparticles were observed as particles having the clear spherical, hexagonal and rod-like morphologies. The crystallite sizes of ZnO spherical and hexagonal particles were in the range of 5-20 nm. ZnO nanorods were found to be ranging from 5-20 nm in width and 20-40 nm in length. The optical properties of ZnO samples were evaluated in term of UV-vis absorption spectra. ©2010 IEEE.